(3aJM GdHGQj aj PcQ eG ENJU Gddg Hg GdTjN RcQjG GdCfUGQjs - (3eQGO Hf jhSa LGhjT GdQhej Ke GdeUQj, GdeYQha HGdCRgQj,J (B1030 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hcai hSdGe Ydi YHGOg GdPjf EUWai GdPi Yde BOe GdCSeGA hGNJU eMeOkG Udi Gddg Ydjg hSde HGdeMHI hGdeYQGL GdCSfi s
(3BNQgG (B:s
(3hjVYg Ydi Jdc GdefGSHI MbjbI hGdMeO ddg hcai hSdGe Ydi YHGOg GdPjf EUWai , hcGf GdaQGZ ef cJGHg eDdagG aj jhe GdLeYg SfI (B1045 (3hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdejkG cKjQkG Edi jhe GdOjf s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B199 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B215s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B304 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs